Interventions with Music in PECTus excavatum treatment (IMPECT trial): a study protocol for a randomised controlled trial investigating the clinical effects of perioperative music interventions - René M H Wijnen; John Vlot; Joost van Rosmalen; Marten J Poley; Markus F Stevens; Ryan J Billar; A Y Rosalie Kühlmann; J Marco Schnater; Jeremy J P Tomas; Gerda W Zijp; Mandana Rad; Sjoerd A de Beer; et al. (BMJ Open)
Introduction Pectus excavatum repair is associated with substantial postoperative pain, despite the use of epidural analgesia and other analgesic regimens. Perioperative recorded music interventions have been shown to alleviate pain and anxiety in adults, but evidence for children and adolescents is still lacking. This study protocol describes a randomised controlled trial that evaluates the effects of recorded music interventions on postoperative pain relief in children and adolescents after pectus excavatum repair.Methods A multicentre randomised controlled trial was set up comparing the effects of perioperative recorded music interventions in addition to standard care with those of standard care only in patients undergoing a Nuss procedure for pectus excavatum repair. One hundred and seventy subjects (12–18 years of age) will be included in three centres in the Netherlands. Patient inclusion has started in November 2018, and is ongoing. The primary outcome is self-reported perceived pain measured on the visual analogue scale. Secondary outcomes are anxiety level, analgesics consumption, vital parameters such as heart rate, blood pressure and respiratory rate, length of hospital stay, postoperative complications, quality of life and cost-effectiveness.Ethics and dissemination This study is being conducted in accordance with the Declaration of Helsinki. The Medical Ethics Review Board of Erasmus University Medical Centre Rotterdam, The Netherlands, has approved this protocol. Results will be disseminated via peer-reviewed scientific journals and conference presentations.Trial registration number NL6863